Strategi Ketidaksantunan dalam Film “Siap, Gan!” - Putri, Nabila Destya; Pribalisty, Nesa Aureola; Hidayati, Mardliyyah; Jaya, Mido Mashela; Lukman, Lukman; Nugroho, Miftah (Universitas Tidar, 2024)
The politeness of speech acts can be influenced by certain sociological factors, for example, relative power, social distance, and the presence of elements of coercion. In its development, politeness in speech acts also develops in its opposite form, namely impoliteness. The focus of the study in this research is the language impoliteness strategy in the film